Critical success factors for Independent Power Producers bank-ability in a volatile economy - Mwasiswebe, Denny (My University, 2019)
Background: The majority of licensed Independent Power Producers (IPPs) are struggling to reach bankability. Published literature has provided evidence that a critical success factor (CSF) approach is a useful tool to differentiate between IPPs that have succeeded and those that failed. Aim: The aim of the study is to identify CSFs in order to improve IPP bankability performance in Zimbabwe. Setting: A deductive research approach was used to investigate why some IPPs succeeded in achieving bankability, while others have failed. Zimbabwe is experiencing incessant power shortages due to ageing electricity generating infrastructure. The policymakers realised the need for private investors and IPPs to provide the additional electricity generating capacity. Methods: The study is based on a new venture creation framework. Quantitative statistical methods were used for hypothesis testing, comparisons, and correlations. Results: The CSFs for improving IPP bankability performance were: environmental risks and challenges; organisational factors; and entrepreneurial behaviours. Conclusion: The study has defined a conclusive framework for IPP bankability performance and it consisted of three CSFs and 19 success factors. This study has recommended that the key stakeholders should use the proposed framework as a starting point, to ensure that unsuccessful private investment outcomes for IPPs are minimised. Keywords: Independent power producer, Critical success factor, Bankability, Power sector, Static framework, Volatile economy, Zimbabwe
MBA
Keywords: Success in business. Entrepreneurship.